PENGARUH RAGAM ALAT BANTU TERHADAP MOTIVASI DAN KETERAMPILAN GERAK DASAR LONCAT HARIMAU - Tangguh Abiyoga; Herman Tarigan; Frans Nurseto (JUPE (Jurnal Penjaskesrek), 2013)
This study aims to determine the increase in motivation and basic movement skills using a variety of tiger sprong aids in son eighth grade students of SMP Negeri 1 Sumberejo the Academic Year 2012/2013. It uses a variety of learning tools. The method used in this study is the experimental method, ie, with 16 sessions.The subjects in this study were students of SMP Negeri 1 Sumberejo son who totaled 28 students.. From the analysis it can be concluded that learning basic movement tiger sprong with a variety of tools using all assistance is 73.4 higher than the basic movement skills using a variety of jump tiger without tools 65.1, using a variety of learning tools can affect students' motivation is 74.5 higher than the average value of motivation in learning that do not use tools range 67.2, there is a significant relationship using a variety of learning tools for students' motivation is evident calculation results obtained koefisine determination (r2 = 0.8412 ) = 0.71 This means using a variety of learning tools can contribute 71% of the students' motivation.Kata kunci : alat bantu, motivasi belajar, loncat harimau